The Correlation of Involvement in Resident Education and Episiotomy Rates [28K]. (May 2018) - Neace, Sasha; Crisp, Catrina; Devaiah, Ganga; Marcotte, Michael; Voss, Deward; Holbert, Michael
Abstract : INTRODUCTION: Nationally, there exists large variation in episiotomy rates among organizations and providers. The Leapfrog group has set a national goal of reducing episiotomy rates to less than 5%. The purpose of this study was to compare rates of episiotomy for providers during their private deliveries who participated in obstetric resident supervision to the rates for providers who did not supervise residents. METHODS: This is a retrospective study examining all private vaginal deliveries performed by physicians at an academic institution from July 1, 2015 to June 30, 2016. Deliveries with shoulder dystocia were excluded. Physician demographic information and delivery attributes were collected and analyzed. RESULTS: There were 3, 785 private vaginal deliveries performed by 68 physicians during the study period: 31 provided resident coverage. Those providing resident supervision performed 1, 578 private deliveries compared to 2, 207 private deliveries among the 37 physicians not providing resident supervision. Physicians providing resident supervision performed half as many episiotomies compared to the group not involved in resident supervision, 7.5% versus 14.5% (OR 0.477, P <.001, 95% CI 0.382–0.595). There was no significant difference in physician demographics or operative vaginal delivery rates between the two groups. CONCLUSION: At our organization, there exists a difference in episiotomy rates among physicians that provide and do not provide resident supervision. Although causality cannot be inferred from this retrospective study, physician involvement in obstetric resident training is associated with reduced episiotomy rates reflecting an improved quality of obstetric care based on one of the Leapfrog group's metrics.